The Role of Open Innovation As a Moderator in the Relationship between Organizational Ambidexterity and Organizational Performance in the Jordanian Government Sector Environment - Ibrahim Al Dwairi, Reham; Abd`Eltwab Hashem, Abd`Elazez; Ahmed Hana, Hossam (Jordan Journal of Business Administration, 2025)
This study explores the impact of open innovation on the relationship between organizational ambidexterity and organizational performance in 25 public independent institutions in Jordan via structural equation modeling. Data was gathered through a questionnaire given to 392 employees in the upper, middle, and heads of departments in these organizations using a simple random probability sample. The sample was tested via cross-sectional data only once and at one time within the period (May 2023/October 2023). This study measured the organization's performance based on balanced scorecards that include both financial and non-financial perspectives. The study suggests that organizational ambidexterity has a positive effect on organizational performance. Open innovation contributes to raising organizational performance. The results indicated that there is no moderating role for open innovation in the relationship between organizational ambidexterity and organizational performance. This study contributed to the resource-based theory by testing it by adding the external resources acquired from the network to which the organization belongs to the resources possessed by this organization that achieve competitive advantage. It introduced the concept of open innovation, which connects organizations with their external environment, so that they can provide their internal resources and thus positively affect the application of organizational ambidexterity and then organizational performance.